93 Telemedicine Implementation in Croydon Care Homes. (6th February 2020) - Smith, J; Tunbridge, R; Houser, K; Serdoz, D
Abstract: Background: Croydon has one of the largest numbers of care homes of any London borough. Following the success of telemedicine in the Airedale and Partners NHS vanguard, care home telemedicine has been commissioned in Croydon. Despite encouraging results for some individual services, the formal evidence base for telemedicine remains ambiguous. We aim to further our understanding of the use, perceptions and implementation of the telemedicine service in the care homes of Croydon. Methods: Results are being collected from care homes including: Usage (e.g. time of day, patient/caller intention) Outcomes (e.g. GP calls, conveyances to hospital) In addition, a survey of GPs and care homes was completed, with redistribution of the survey planned six months after introduction of telemedicine. Results: In the first four months data of the service, 42 care homes have implemented telemedicine since Jan 2019. For these care homes, the results show a reduction in ambulance call outs of 7% and a reduction in conveyances to hospital of 4%. In the care homes that have been using the service on a regular basis, the reduction in call outs and conveyances is considerably bigger. There is also increasing use of the telemedicine service in preference to calling a GP. This data will become more robust and analysed further with the ongoing use of the service. Initial survey results highlight the varied opinions of telemedicine, including perceived change in workload and quality of care, and will be repeated in August 2019 to assess any change in perceptions. Discussion: The emerging data shows encouraging results for those care homes that are high users of telemedicine service. However, there is significant time and resource involved to ensure uptake and correct use of telemedicine in care homes. With the survey, we have uncovered a varied understanding and perception of telemedicine across the Croydon system prior to its implementation in care homes and will discover if these perceptions change following its increasing use. We will present the successes and challenges to the implementation of the telemedicine service in care homes so far, then discuss the opportunities for care home telemedicine in Croydon for the future.